Colonization factor CS30 from enterotoxigenic Escherichia coli binds to sulfatide in human and porcine small intestine. Issue 1 (31st December 2020) - Von Mentzer, Astrid; Zalem, Dani; Chrienova, Zofia; Teneberg, Susann
ABSTRACT: The ability to adhere via colonization factors to specific receptors located on the intestinal mucosa is a key virulence factor in enterotoxigenic Escherichia coli (ETEC) pathogenesis. Here, the potential glycosphingolipid receptors of the novel human ETEC colonization factor CS30 were examined by binding of CS30-expressing bacteria to glycosphingolipids on thin-layer chromatograms. We thereby found a highly specific binding of CS30-expressing bacteria to a fast-migrating acid glycosphingolipid of human and porcine small intestine, while no binding was obtained with a mutant ETEC strain unable to express CS30 fimbriae. The CS30 binding glycosphingolipid from human small intestine was isolated and characterized by mass spectrometry as sulfatide (SO3 -3Galβ1Cer). Comparative binding studies using sulfatides with different ceramide compositions gave a preferential binding of CS30 to sulfatide with d18:1-h24:0 ceramide. This ceramide species of sulfatide was also isolated from human small intestine and characterized by mass spectrometry and antibody binding. These studies implicate sulfatide as candidate receptor for mediating attachment of CS30-fimbriated ETEC to human and porcine small intestinal cells. Our findings may be a basis for designing receptor saccharide analogues for inhibition of the intestinal adhesion of CS30-expressing E. coli .